Unique challenges in urban schools : the involvement of African American parents - Jackson, Eric, 1965-; Turner, Carolyn; Battle, Dorothy E. (Rowman & Littlefield, 2015)
This study explores the various ways in which parental involvement can help to increase student academic success. More specifically, this analysis is based on the notions that parent involvement in inner city schools present unique challenges that are different from the traditional middle class perspective.